Supervisory Systems, Fiscal Soundness and International Capital Movement: More Challenges for new EU Members - Andreas Grünbichler; Patrick Darlap; Sinikka Salo; Leslie Lipschitz; Timothy Lane; Alex Mourmouras (SUERF - The European Money and Finance Forum, 2004)
On May 1, 2004, ten countries in Central, Eastern and Southern Europe will become full members of the EU. The parliaments and monetary authorities of the ten accession countries have already to a large extent adapted their legal and institutional structures to the new Europe-wide environment. The papers in this SUERF Study analyse from different perspectives the challenges to regulators, supervisors, Governments and central bankers that are related to safeguarding financial stability in a large economic union with financial markets that are open to global competition. The papers were presented in March 2003 at a seminar jointly organised by SUERF and the Central Bank of Malta.
Keywords: E4; E6; F3; G15; G18; G28; H6; H11; H77; L51; 330; Regulatory Integration; Supervisory Design; fiscal theory of price level; EU accession countries; Central and Eastern Europe; capital flows; convergence; macroeconomic policy; Bankenaufsicht; Versicherungsaufsicht; EU-Recht; EU-Staaten